One multivalued discrete system and its properties - Komleva, T. A.; Plotnikov, A. V.; Plotnikova, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider one multivalued discrete system and study its properties and the existence of its solution.